The effect of consumers’ attitudes towards logos or emblems on brand preference - DENEÇLİ, Sevda (My University, 2015)
This study, which has attempted to identify the effects of the attitude of consumers towards the brand logos or emblems on their preference for particular brands, has been carried out on 127 people through convenience sampling. Within the scope of the study, two international sports clothing brands, which are the most popular in the Turkish market, have been discussed, one of these using logos and the other using emblems. In the study, correlation analysis has been used to identify the relationship between the attitudes of consumers towards the logos and emblems of brands which use one or other of them and their preference between brands, while multiple regression analysis has been used to identify the effect of the attitude of consumers towards the logos and emblems of brands on their preference for particular brands. In this manner, the effect of the use of logos or emblems by brands on brand preference is analysed comparatively, by taking into consideration individuals who use or do not use brands which use logos or individuals who use or do not use brands which use emblems.
Keywords: Logo; Emblem; Brand; Brand Preference